Determinants of Malaria Re-emergence in Coastal and Island Elimination Settings: A PRISMA-Based Systematic Review - Rahmah RA AZ; Mursid Raharjo; Sulistiyani (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2026)
Introduction: Malaria elimination remains vulnerable in receptive coastal and island settings where ecological change, vector adaptation, human mobility, imported infections, surveillance gaps, and governance constraints may interact. This systematic review aimed to synthesize determinants of malaria re-emergence, resurgence, reintroduction, and re-establishment of local transmission in coastal and island elimination settings, with relevance to Indonesia and other tropical archipelagic regions. Method: A systematic review was conducted following PRISMA 2020 guidelines. Literature was searched in Scopus, ScienceDirect, and PubMed for studies published from 2019 to 2025. Eligible studies addressed malaria re-emergence, elimination sustainability, ecological receptivity, vector or parasite factors, imported transmission, surveillance capacity, or governance issues in coastal, island, archipelagic, low-transmission, or elimination-related contexts. From 1,054 identified records, 30 studies met the inclusion criteria and were synthesized thematically. Result: Malaria re-emergence in coastal and island elimination settings was not attributable to a single determinant. Ecological and climatic factors, including land-use change, wetland formation, coastal modification, rainfall variability, and rising temperature, may increase suitable habitats for Anopheles vectors. Vector behavioral adaptation, outdoor biting, altered resting behavior, and insecticide resistance may reduce the effectiveness of indoor-based interventions. Human mobility through migration, fishing, mining, tourism, port activity, and inter-island travel may facilitate parasite importation into receptive areas. Plasmodium vivax relapse, low-density infection, and asymptomatic carriage may further complicate case detection and classification. Surveillance weaknesses, limited molecular diagnostic capacity, delayed investigation, fragmented reporting, unstable financing, and weak intersectoral coordination may reduce elimination resilience. Conclusion: Sustaining malaria elimination in coastal and island settings requires integrated, adaptive surveillance linking epidemiological, entomological, climatic, mobility, and laboratory data. Strengthening port-based surveillance, vector monitoring, molecular diagnostics, community participation, intersectoral coordination, and sustainable financing is essential to prevent reintroduction and local transmission re-establishment.